2020
DOI: 10.1111/sode.12444
|View full text |Cite
|
Sign up to set email alerts
|

Unsociability, peer relations, and psychological maladjustment among children: A moderated‐mediated model

Abstract: The goal of this study was to evaluate a complex theoretical model linking gender, unsociability, peer relations, and indices of psychological maladjustment among children in the People's Republic of China. Participants were 711 (395 boys) Grade 4 to Grade 8 (M age = 10.98 years, SD = 1.56) students selected from 4 public schools in Shanghai. Multisource assessments were employed, including peer nominations of unsociability, sociometric nominations to measure peer preference, as well as child self-reports of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 87 publications
(145 reference statements)
0
16
0
Order By: Relevance
“…However, massive economic changes and social reforms in China over the last 25 years, particularly in urban centers, have resulted in the adoption of many individualistic values (e.g., assertiveness), which appear to have made shyness a more maladaptive characteristic (Xiao & Coplan, 2021). In support of this notion, results from contemporary studies of shyness among Chinese children and adolescents consistently indicate that shyness is now associated with internalizing problems (e.g., loneliness, depression, low self‐worth), negative peer experiences (e.g., rejection, victimization), and academic difficulties (e.g., poorer academic achievement; Bullock et al, 2020; Ding et al, 2014; Ding et al, 2020; Liu et al, 2019; Zhang & Eggum‐Wilkens, 2018).…”
Section: Introductionmentioning
confidence: 93%
“…However, massive economic changes and social reforms in China over the last 25 years, particularly in urban centers, have resulted in the adoption of many individualistic values (e.g., assertiveness), which appear to have made shyness a more maladaptive characteristic (Xiao & Coplan, 2021). In support of this notion, results from contemporary studies of shyness among Chinese children and adolescents consistently indicate that shyness is now associated with internalizing problems (e.g., loneliness, depression, low self‐worth), negative peer experiences (e.g., rejection, victimization), and academic difficulties (e.g., poorer academic achievement; Bullock et al, 2020; Ding et al, 2014; Ding et al, 2020; Liu et al, 2019; Zhang & Eggum‐Wilkens, 2018).…”
Section: Introductionmentioning
confidence: 93%
“…In collectivistic societies, people with a high preference for solitude may be seen as unsociable, and they are more likely to be evaluated negatively and therefore being excluded or isolated. These negative experiences could lead to a series of psychological distress, including depressive symptoms, anxiety, and stress (Wang et al, 2013b;Ladd et al, 2018;Bullock et al, 2020). In addition, according to the Psychological Decompensation Hypothesis (Gao and Chen, 2006) and Compensatory Internet Use Theory (Kardefelt-Winther, 2014), psychosocial problems, such as psychological distress, are one of the basic motivations for individuals' use of Internet or mobile phones.…”
Section: Discussionmentioning
confidence: 99%
“…These negative life events were positively associated with stress, depression, and anxiety (Ladd et al, 2018). An empirical study also found that preference for solitude could predict psychological maladjustment through peer difficulties among Chinese children (Bullock et al, 2020). Therefore, individuals with high preference for solitude may experience more psychological distress owing to interpersonal difficulties.…”
Section: The Mediating Role Of Psychological Distressmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies showed positive relations between depressive symptoms and PFS in both West (e.g., Barstead et al, 2017;Wang et al, 2013) and China (e.g., Bullock et al, 2020;Liu et al, 2017;Wang, 2016). Most of the research was conducted under the premise that aspects of maladaptive peer relationships, such as PFS, were a precipitant, rather than a consequence, of depression (e.g., Chen et al, 2011;Liu et al, 2014;Wang, 2016).…”
mentioning
confidence: 99%